2008
DOI: 10.11606/issn.2176-7262.v41i2p188-195
|View full text |Cite
|
Sign up to set email alerts
|

Classificação Histopatológica E Correlação Clínica De 50 Casos De Hanseníase Diagnosticados Em Um Hospital-Escola, São José Do Rio Preto, Sp

Abstract: Foram revistos 50 pedidos de biópsia e analisadas as lâminas coradas pelos métodos H&E e Ziehl-Neelsen, utilizando os critérios de Ridley & Jopling. Resultados: As formas classificadas foram: 9 indeterminadas, 10 tuberculóides, 5 dimorfas tuberculóides, 5 dimorfas lepromatosas, 5 subpolares lepromatosas e 16 lepromatosas. Dos 50 pacientes, 30 eram do sexo masculino, e as formas multibacilares predominaram nesse sexo. Em 2 não se fez hipótese diagnóstica de Hanseníase, e em 30 foi especificada uma ou mais forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…11,12 However, if the direct smear microscopy test is available, patients who present positive dermal smears will be classified as multibacillary, regardless of the number of skin lesions. [13][14][15] A correct classification makes it possible to institute appropriate treatment and decreases the transmission of the disease, as well as the chances of recurrence, physical disability, and deformity. 5,7,8,15,16 Deformities can bring problems like reduced ability to work and limitations in the person's social life, and are responsible for the stigma and prejudice against this disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 However, if the direct smear microscopy test is available, patients who present positive dermal smears will be classified as multibacillary, regardless of the number of skin lesions. [13][14][15] A correct classification makes it possible to institute appropriate treatment and decreases the transmission of the disease, as well as the chances of recurrence, physical disability, and deformity. 5,7,8,15,16 Deformities can bring problems like reduced ability to work and limitations in the person's social life, and are responsible for the stigma and prejudice against this disease.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] A correct classification makes it possible to institute appropriate treatment and decreases the transmission of the disease, as well as the chances of recurrence, physical disability, and deformity. 5,7,8,15,16 Deformities can bring problems like reduced ability to work and limitations in the person's social life, and are responsible for the stigma and prejudice against this disease. 13,16 However, studies have shown that difficulties in establishing the correct classification exist, and have also demonstrated a lack of concordance between the clinical and histopathological classifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os diagnósticos diferenciais das lesões hipomelanóticas cutâneas temos: a) líquen escleroso: clinicamente se manifesta com pápulas hipopigmentadas que se coalescem e formam placas, predominantemente na região genital (2,4) ; histologicamente, apresenta esclerose dérmica patognomô-nica associada a infiltrado liquenóide, e a leucodermia parece estar mais associada à diminuição de produção de melanina do que à perda de melanócitos, pois a imuno-histoquímica mostra que somente raros casos têm perda significativa de melanócitos como observado no vitiligo (4) ; b) lúpus eritematoso vitiligóide: máculas atróficas hipocrômicas ou acrômicas podem ser observadas, especialmente nas formas discóide ou subaguda; no exame anatomopatológico observam-se hiperceratose com formação de "rolhas" córneas, atrofia da epiderme, espessamento e tortuosidade da membrana basal, infiltrado liquenóide ao longo da junção dermoepidér-mica e ao redor dos folículos pilosos, extravasamento de eritrócitos e depósitos de mucina intersticial. E no estudo imuno-histoquímico é observada perda parcial de melanócitos (19) ; c) pitiríase alba: apresenta-se como área hipocrômi-ca circinada ou oval, com descamação fina superficial, predominantemente na face e em indivíduos de idade pré-escolar ou escolar; a histologia mostra melanófagos na derme em meio a infiltrado linfocitário e agressão da junção dermoepidérmica, não sendo observada perda de melanócitos à imuno-histoquímica (21) ; d) hanseníase: manifesta-se como mácula hipocrômica, hipoestésica ou anestésica, caracterizada por inflamação granulomatosa da derme, com presença de bacilos álcool-ácido-resistentes detectados pela coloração de Fite-Faraco (17) ; e) sarcoidose: clinicamente se manifesta como pápu-las, comumente na face, que podem ser hipocrômicas; e na biópsia são observados granulomas não-caseosos (7) .…”
Section: Discussionunclassified
“…Leprosy was diagnosed based on clinical and bacteriological observations and classified according to Madrid Classification. The Madrid classification is based on clinical and bacilloscopic characteristics, dividing leprosy into two unstable groups, indeterminate and dimorphic or borderline, and two stable types, tuberculoid and lepromatous polar [ 16 ].…”
Section: Methodsmentioning
confidence: 99%